From biomass resources to functional materials: A fluorescent thermosetting material based on resveratrol via thiol-ene click chemistry. (15th January 2020) - Tian, Yazhou; Wang, Qiong; Wang, Kun; Ke, Meng; Hu, Yujing; Shen, Lijiao; Geng, Qiangwang; Cheng, Jue; Zhang, Junying
Graphical abstract: Highlights: Resveratrol allyl ether (RAE) was prepared from sustainable feedstocks. A series of thermosetting materials were designed via thiol-ene click reaction. RAE/4SH exhibited the highest T g and mechanical properties. RAE/4SH performed exceptional blue-fluorescence under the excitation of UV-light. MTT and cell experiment confirmed low-toxicity of RAE/SH. Abstract: Exploring sustainable biobased thiol-ene crosslinked networks with inherent fluorescence, high comprehensive properties as well as low-toxicity will significantly expand their applications in display, anti-counterfeiting, and biomedical materials, etc. In this work, resveratrol allyl ether (RAE), a novel multifunctional allyl compound, was prepared from sustainable feedstocks, and a series of thermosetting materials were designed by tuning the functionality of thiol compounds (from two to four) via UV-light induced thiol-ene click reaction. The curing behavior, thermal and thermomechanical performance, mechanical properties, and biotoxicity of these thiol-ene crosslinked networks were investigated, respectively. Results showed that RAE-4SH exhibited the highest T g and mechanical properties. Specifically, the T g of RAE-4SH was up to 71.2 °C; meanwhile, the tensile strength and modulus were as high as 49.5 MPa and 1.2 GPa, respectively. Interestingly, it also performed exceptional strong blue-fluorescence under the excitation of UV-light due to the inherent conjugated structure. Moreover, the MTT and cell experiment confirmed low-toxicity of RAE-4SH. Finally, several complex patterns including "BUCT", a flower, and a two-dimension code can be easily prepared with the help of the photo mask. To summarize, RAE provides a new strategy to explore the biomass resources to prepare high-performance functional materials, which may greatly enlarge its application in the future.